Common surgery, uncommon complication - Hande Akdeniz (Mattioli1885, 2015)
Ingrown nail surgery is the one of the most common surgeries in outpatient clinics that are generally perfomed in response to patient complaints. Still, making simple observations, taking patient histories and conducting further tests are often neglected by outpatient clinics. Consequently, it is important to be aware if ingrown nail is associated with any underlying diseases that can lead to major complications.